Model Spasial Level Dasar Bangunan Kota Tepian Air (Studi Kasus: Kota Makassar) - Sudirman Nganro; Slamet Trisutomo; Roland Alexander Barkey; Mukti Ali; Nurjannah Nurdin (Diponegoro University, 2020)
Flooding is a threat to coastal cities such as Makassar City. To Avoid the threat of flooding, it is necessary to determine the ground level of the building. This study aims to develop a spatial model for determining the ground level of buildings for Makassar City based on climate change data and environmental geography. Prediction of sea level rise using MAGICC/SCENGEN application, GIS-based satellite image analysis, rainfall analysis using Thiessen polygon method, surface runoff coefficient value determined by Cook method, and design flood discharge analysis with HSU Nakayasu method. The spatial model of the ground level of Makassar City building for 2030 is a function of sea tides, sea level rise due to climate change, alluvial floods and inflow floods that can occur simultaneously. The model produces a spatial map with attributes of geographic coordinates (x,y,z).